A COMPUTATIONAL REAL-TIME VIRTUAL ENVIRONMENT MODEL FOR CROWD MANAGEMENT - AGYEI; JANET SERWAA LAH, ENDURANCE APPIAH; DAN SOAH ROSE OPPONG (International Journal of Multidisciplinary Research and Studies, 2020)
During the annual Islamic pilgrimage (Hajj), the movement of vehicles and pedestrians from Arafat to Muzdalifah during the Nafrah of pilgrims is thought to suffer from severe bottlenecks that usually lead to the arrival of thousands of pilgrims to Muzdalifah well after dawn. This paper proposes a framework for developing an intelligent real-time virtual environment model for facilitating efficient and timely vehicular traffic movement during the Nafrah utilizing various movement scenarios, simulation, and optimization methods. The model utilizes intelligent agents within a real-time 3D virtual environment that represents the Nafrah from Arafat location coverage. The proposed framework has three primary phases each of which has specific components: (a) spatial analysis of current pedestrians and vehicles access within the Nafrah location coverage from Arafat to Muzdalifah; (b) evaluation of movement efficiency of current scenarios of the Nafrah using computational simulation; and (c) development of a multi-agents system within a real-time 3D virtual environment for improving the movement efficiency of vehicles traffic within the Sarah. The proposed model will be utilized by decision-makers (Hajj authorities) during the Nafrah from Arafat to Muzdalifah to attain an efficient performance of crowd management.